Improved search for a Higgs boson produced in association with Z → l+ l- in pp collisions sqrt[s] = 1.96 TeV. - Aaltonen, T; González, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Appel, J; Apresyan, A; Arisawa, T; Artikov, A; et al. (2010)
We search for the standard model Higgs boson produced with a Z boson in 4.1 fb(-1) of integrated luminosity collected with the CDF II detector at the Tevatron. In events consistent with the decay of the Higgs boson to a bottom-quark pair and the Z boson to electrons or muons, we set 95% credibility level upper limits on the ZH production cross section multiplied by the H → bb branching ratio. Improved analysis methods enhance signal sensitivity by 20% relative to previous searches. At a Higgs boson mass of 115 GeV/c2 we set a limit of 5.9 times the standard model cross section.